Modelling and interpretation of SEDs* - Woitke Peter (EPJ Web of Conferences, 2015)
Circumstellar disks are mostly detected by larger continuum fluxes in the infrared to mm spectral regions as compared to naked stars (a flux excess). The analysis of the Spectral Energy Distribution (SED) of that flux excess was crucial for the development of the first theories about protoplanetary disks, and even nowadays, it is still one of the major tools to physically characterise the disks in terms of their mass, inner holes and gaps, vertical extension & shape, dust properties, and evolutionary state. In this chapter, we will review some of the early simple theories, show some examples, discuss the influence of typical disk shape and dust size parameters in modern SED analysis, and discuss how degenerate the results can be.